Evaluation of Novel Gerbera (Gerbera jamesonii Bolus ex. Hooker F.) Hybrids for Flower Quality Traits under Naturally-Ventilated Polyhouse - C Aswath (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2016)
The present study was carried out to evaluate performance of two gerbera hybrids IIHR 3-34 and IIHR 8-45 along with their parents and check, for flower quality traits under naturally-ventilated polyhouse in Randomized Block Design, in the years 2014-15 and 2015-16. Both the hybrids had been developed through the half-sib method of breeding with IIHR-3 and IIHR-1, respectively, as parents. Data for the two years were pooled and analyzed statistically. Significant differences were observed in the quality traits studied. In the case of both hybrids IIHR 3-34 and IIHR 8-45, most of the quantitative traits were found to be on par with the check variety, Elite. They had novel flower colour (68D as per RHS Colour Chart), Red Purple Group (IIHR 3-34) and 50A Red Group (IIHR 8-45), with double type of flowers. These are suitable for cut-flower and flower arrangement purposes. These hybrids will prove useful for developing more gerbera hybrids with novel traits.